Digitization of Endocytic pH by Hybrid Ultra-pH-Sensitive Nanoprobes at Single-Organelle Resolution - Wang, Yiguang (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.